Ecoturismo e Comunicazione Intergenerazionale Interculturale (Altre Modernità, 2012)
Since the first research carried out by the Generational Encounters Laboratory  of the University of Milan (1998) on I. T. languages and intergenerational communication and having as primary aim the one shown by the research projects carried out during the academic years 1998-1999: “socializing the generations by socializing the institutions” (Albanese, 1999, 2000); during 2002-2010 in Viterbo experimental research of intergenerational tourism and environmental education took place.The central Italy experiences/researches are characterized by:•    the choice of a particular type of tourism: thermal tourism;•    the presence, during the years 2003-2007, of teenagers with different nationalities; the cross cultural meeting has been implemented so together with the intergenerational one.In the following article, we will display some of the main results obtained thanks to the experimental/researches, particularly with reference to the communication data, collected in the inter-generational and cross-cultural communication area.